0
$\begingroup$

I currently read the paper of Guifre Vidal about Entanglement Monotones (link). On page 5 he states the following theorem:

Theorem 1 The maximal probability of success $P(\rho \rightarrow \rho*)$ in the converion of $\rho \rightarrow \rho*$ that the parties can achieve by means of a strategy involving only LQCC [local quantum operations assisted with classical communication] is given by $$P(\rho \rightarrow \rho*)=\min \frac{\mu(\rho)}{\mu(\rho*)}$$ where the minimization is performed over the hole set of all Entanglement Monotones $\mu$.

The proof of this theorem is very short and it seems obvious from Vidal's point of view, but I don't understand it. Can anyone help me to understand this?

$\endgroup$
1
$\begingroup$

Since the probability of success for any strategy is upper bounded by $\mu(\rho)/\mu(\rho^*)$ as seen in eq (14), this will in particular also hold for the strategy that achieve the maximal probability of success $P[\rho\rightarrow\rho^*]$. Note that eq. (14) holds for any entanglement monotone $\mu$ so the entanglement monotone that minimise $\mu(\rho)/\mu(\rho^*)$ is therefore also an upper bound. This means we have the following inequality, $$P[\rho\rightarrow\rho^*]\leq\min_{\mu}\frac{\mu(\rho)}{\mu(\rho^*)}.\tag{I}$$ We now need to show that this is actually an equality. One way to see this is to first note that $$\min_{\mu}\frac{\mu(\rho)}{\mu(\rho^*)}\leq\frac{\mu'(\rho)}{\mu'(\rho^*)}\tag{II}$$ for any fixed entanglement monotone $\mu'$. Then we can use the fact that $P[\rho\rightarrow\rho^*]$ defines an entanglement monotone given by $$\mu_{\rho^*}(\rho)=P[\rho\rightarrow\rho^*].\tag{III}$$ Putting this into equation (II) we have that $$\min_{\mu}\frac{\mu(\rho)}{\mu(\rho^*)}\leq\frac{\mu_{\rho^*}(\rho)}{\mu_{\rho^*}(\rho^*)}=\frac{P[\rho\rightarrow\rho^*]}{P[\rho^*\rightarrow\rho^*]}=P[\rho\rightarrow\rho^*]\tag{IV}$$ where we used that $P[\rho^*\rightarrow\rho^*]=1$. Finally putting this into equation (I) we have that $$\min_{\mu}\frac{\mu(\rho)}{\mu(\rho^*)}\leq P[\rho\rightarrow\rho^*]\leq \min_{\mu}\frac{\mu(\rho)}{\mu(\rho^*)}\tag{V}$$ which implies that $$P[\rho\rightarrow\rho^*]=\min_{\mu}\frac{\mu(\rho)}{\mu(\rho^*)}\tag{VI}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.